Analysis of the vicugna pacos (Alpaca) wool fiber in the properties of concrete - Acevedo Villazana, Levi (2023)
This research aimed to analyze alpaca (Vicugna pacos) wool fiber as a reinforcement in the properties of concrete. For this purpose, methodologies such as ASTM (American Society for Testing and Materials), ACI ( American Concrete Institute), and Peruvian Technical Standards (NTP) were used; likewise, the experimental design methodology was employed. The sample consisted of 45 specimens; 30 were cylindrical, and 15 were in the form of beams. The alpaca wool fiber was used in percentages of 0%, 0.5%, 1%, 2%, and 4%, with 60 mm length cuts added to the concrete mix. The results showed that the compressive strength in the specimens containing the alpaca wool fiber at 28 days complies with the percentages established by the ACI standard. However, the compressive strength of 33.48% was decreased in the control specimen. As for the tensile strength, compared to the control specimen, an average increase of 1.19% was observed on day 28. Finally, compared to the control specimen, the values obtained in the flexural strength of the alpaca wool fiber specimens showed an average reduction of 19% and 18% on days 14 and 28, respectively. In conclusion, when analyzing the samples containing the alpaca wool fiber, we observed that the tensile strength improved thanks to alpaca wool fibers.